Logging Waste-a Potential Source Of Energy - Kant, Hari (Indian Forester, 1981)
The world is facing energy crisis. Efforts are being made to find alternative sources of energy. Forests provide energy in the form of fuelwood and charcoal. Present harvesting techniques are very wasteful. Energywise, the logging waste on account of billeting of fuelwood by axe alone is equivalent to 4,72,200 wagons of soft coke Or 7041.8 megawatt hours of electricity, which is six times the installed capacity of Bhakra-Nangal Dam. Wood waste in the form of chips left in the coniferous forests on account of in-situ conversion is equivalent to another 0.4 million m3 of fuelwood. In some areas eg. Andamans islands, lot of wood is left behind in the forest as logging residue. It can be used for charcoal manufacture and supply to distant places. If requisite infrastructure is developed in the potentially exploitable are not utilised so far, about 6.05 million m3 of fuelwood (eqivalent to 36 million tonnes of soft coke or 2720 megawatts of electricity) can be made available. Replacement of axe by saw and development of infrastructure in the remote areas will be useful in meeting the energy shortage to a great extent.